2014
DOI: 10.1016/j.ijlp.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone reactivity and identification with a perpetrator or a victim in a story are associated with attraction to violence-related cues

Abstract: a b s t r a c t Keywords:Appetitive aggression Testosterone IAPS pictures Violent story Background: Recent field research has demonstrated that an attraction to aggressive behavior and cruelty is com mon among combatants and perpetrators involved in organized violence. The biological basis of this appetitive perception of aggression in humans has to date not been studied. Aims: We examined testosterone as a potential hormonal moderator during induction of specifically appetitive aggressive behavior in the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Additionally, women found the simulated scent of blood more arousing than men, but this was only for those women who rated the scent as negative. Thus, although the literature suggests that women can be more sensitive to withdrawal cues [ 22 ], including olfactory cues [ 23 , 24 ], our findings limit this specifically to women taking OC. Women without OC rate it more positively, and this is further potentiated by the fertile phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, women found the simulated scent of blood more arousing than men, but this was only for those women who rated the scent as negative. Thus, although the literature suggests that women can be more sensitive to withdrawal cues [ 22 ], including olfactory cues [ 23 , 24 ], our findings limit this specifically to women taking OC. Women without OC rate it more positively, and this is further potentiated by the fertile phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 86%
“…Evolutionary theory suggests that there was more selective pressure on men than women to develop hunting and killing of animals and rival conspecifics [ 7 , 8 ]. Though admittedly speculative, this finds empirical support in that women are more likely to identify with the victim than the perpetrator in the same imagined violent scenario [ 22 ]. Olfactory research examining responses to fear-induced sweat have shown that women are more sensitive to these anxiety cues [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another technique to induce aggression is to use dramatic testimonies, where participants are asked to put themselves in the position of a killer vs. victim (Weierstall et al, 2014 ). This has been shown to increase or decrease testosterone in men, according to whether the person is assigned to take the appetitive (perpetrator) or reactive (victim), role in the story, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates both a satisfactory factorial and criterion validity and sufficient psychometric features (including Cronbach's Alpha = 0.85). Proven to be a valid and reliable questionnaire, it has already been implemented in its original form with female combatants and civilians (e.g., Augsburger et al, 2015; Meyer-Parlapanis et al, 2016) and as a modified self-assessment instrument in civilian populations (e.g., Weierstall et al, 2014). In the current study, the existing items on the AAS were reformulated and adapted to the competitive elements in the sporting context (for example: original item: “Does the challenge of defeating a strong opponent make the fight more pleasurable for you in comparison to the defeat of a weak opponent?” → competitive item: “Does the challenge of winning against a particularly strong team make the game more exciting in comparison with winning against a weak team?”; original item: “When you fight, do you stop caring about whether you could be killed?” → competitive item: “During the game, do you fear that you might be injured or at least give this some thought?”).…”
Section: Methodsmentioning
confidence: 99%